Development of Microbiology Handout as Teaching Material to Improve Science Process Skills of Health Vocational Students - Pratama, Aris Yudha; Hastuti, Utami Sri; Setiowati, Frida Kunti (BIOEDUKASI, 2024)
This research is a research and development of Microbiology Handout on the topic "Antibacterial Test on Bacterial Growth Inhibition" which uses natural materials, namely star fruit extract (Averrhoa carambola L.), which will be used as teaching materials in the learning process to help improve students' science process skills. The purpose of developing Microbiology Handout is to produce teaching materials that are valid, practical and effective for use in learning Microbiology subjects. Microbiology Handout development uses the ADDIE development model. Validation of Microbiology Handouts was carried out by learning media and teaching material expert validators, Microbiology material experts, and Microbiology learning practitioner expert validators. The Microbiology Handout trial was conducted through three stages of trials, namely a one-to-one trial of 3 students, a small group trial of 10 students, and a field trial of 15 students. The effectiveness of Microbiology Handout in improving students' science process skills can be seen through pretest and posttest scores analyzed using the IBM SPSS version 26 application through the One Way Ancova test. The results of research and development show the acquisition of validation scores by learning media and teaching material experts of 100%, Microbiology material experts of 94.3%, education practitioner experts of 99.64%, student response results of 91.43% and efficiency results of 0.028